(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
In order to improve the physical fitness of the Greco-Roman style wrestlers, we also used educational-training exercises in the pedagogical experiment, which varied from the developed complexes, where the educational-training work was built according to the regulated method according to the principle of circular training.